Increased plasma levels of lead in patients with amyotrophic lateral sclerosis compared with control subjects as determined by flameless atomic absorption spectrophotometry. Issue 5 (May 1978) - Conradi, S; Ronnevi, L O; Vesterberg, O
Abstract : The levels of lead in plasma were determined in 16 cases of amyotrophic lateral sclerosis (ALS) and 18 control subjects, using flameless atomic absorption spectrophotometry. The mean values were 0.52+/-0.22 microgram/100ml (ALS) and 0.37+/-0.13 microgram/100ml (controls), the difference is statistically significant (5% level). The values in both groups are lower than reported earlier for normal subjects. The findings are discussed against the background of the possible pathogenetic significance of retrograde axoplasmic flow in ALS.